A brief essay on the avoidance of the aversive control and the bad connotations related to its use (Research, Society and Development, 2024)
An aversive stimulus can be defined as one in which the emission of a response that promotes its removal, prevention or postponement is strengthened or when its presentation decreases the probability of emission of a given response. Behavioral interventions that employ these manipulations are widely questioned and sometimes classified as bad. The “bad” connotation for aversive control arises from the possible harm to the individual or to society, however, such harm may not occur or may also be identified in positive reinforcement. Therefore, the present manuscript consists of a reflective essay that discusses the concept of aversive control and its functional definition based on experimentation and its ethical use in the practice of behavior analysts. It is understood that the use of aversive control, as well as the use of positive reinforcement, must always be based on a careful evaluation by the behavior analyst and this evaluation must be based on experimentation.